Culture, Peers, and Delinquency. - Ferrari, Joseph R. (Taylor and Francis, 2014)
Increase your understanding of the etiology, prevention, and treatment of delinquency! This informative book provides you with specific strategies to assess delinquency and to increase the effectiveness of any prevention program. In addition, it presents a community peer model of delinquency with important implications for delinquency prevention programs and for delinquency research. Examining specific cultural groups in the United States, including Caucasians, East Asians, South-East Asians, Polynesians/Micronesians, and Vietnamese, as well as Japanese youths in their homeland, this.